Estágio curricular supervisionado: um relato de experiência - Imbiriba, Carlos Eduardo Castro (Brasil, 2022)
This is a course conclusion work, in the area of Degree in Physical Education characterized as descriptive and carried out through an experience report in a public school in Manaus. General Objective: to analyze through observations the effects of physical education classes on children's lives. Specific objectives: report the experience lived in the Supervised Curricular Internship; and to present a critical position regarding the role of school physical education in elementary education. Methodology: an intervention was carried out in 24 days, with 5 weekly sessions of 4 hours class, with three observation classes, three participation and seven conducting. The contents were based on the assumption of fundamental motor skills: locomotion, manipulation and stabilization. Results: it was observed that the number of classes provided opportunities for greater experiences for children, making the classes conducted by the interns more masterful and independent of activities. Final considerations: the school provides a considerable number of classes, giving children more opportunities to continue in the area of sports or physical exercises, and it also makes 90% of what is proposed by the World Health Organization viable. That leaves only 10% in activities that need to be done outside of school with the support of friends and family.